Effect of Coloring-by-Dipping on Microtensile Bond Strength of Zirconia to Resin Cement - Minoo Mahshid; Naeem Berijani; Seyed Jalil Sadr; Farhad Tabatabaian; Sepide Sorour Homayoon (Tehran University of Medical Sciences, 2016)
Objectives: Studies on the effect of coloring procedures on the bond strength of zirconia to resin cement are lacking in the literature. This study evaluated the effect of dipping of zirconia ceramic in different liquid color shades on the microtensile bond strength (MTBS) of zirconia ceramic to resin cement. Materials and Methods: This in vitro study was conducted on 100 microbar specimens divided into five groups of B2, C1, D4, A3 and control (not colored). To prepare the microbars, 20 white zirconia ceramic blocks, measuring 5×11×11 mm, were dipped in A3, B2, C1 or D4 liquid color shades for 10 seconds (five blocks for each color shade) and five blocks were not colored as controls. All the zirconia blocks were sintered in a sintering furnace. Composite blocks of similar dimensions were fabricated and bonded to zirconia ceramic blocks using Panavia F 2.0 resin cement. Zirconia-cement-composite blocks were sectioned into microbars measuring 1×1×10 mm. The MTBS of microbars was measured by a testing machine. Data were analyzed using one-way ANOVA and Tukey's test. All tests were carried out at 0.05 level of significance. Results: Statistically significant differences were found among the groups in MTBS (P<0.001). The D4 group had the highest MTBS value (39.16 ± 6.52 MPa). Conclusion: Dipping affected the MTBS of zirconia ceramic to Panavia F 2.0 resin cement; however, a similar pattern of change was not seen due to the different liquid color shades.